Artificial Intelligence in the European approach to Education: Perspectives, perceptions, and mistrust - Salvatore Nizzolino (Pensa MultiMedia, 2024)
This contribution examines the ongoing debate concerning the role of artificial intelligence in education (AIEd), and focuses on the challenges and opportunities posed by the new technologies in the EU. The future perspectives of AIEd in the EU encompass a broad spectrum of ethical, regulatory, educational, and societal considerations, reflecting a proactive and multifaceted approach to addressing the new emerging context. The paper also visualizes the intellectual map of the European academia engaged in AI-related research through bibliometrics, revealing the main topics and gaps in the current debate. The scrutiny reveals a lack of documented practical case studies to support education professionals, while the current debate focuses mostly on ethical and regulatory issues.